2005
DOI: 10.1007/s11136-005-8166-9
|View full text |Cite
|
Sign up to set email alerts
|

How to Measure Self-management Abilities in Older People by Self-report. The Development of the SMAS-30

Abstract: This paper presents the results of two studies carried out in order to design and test a self-report instrument to measure Self-Management Ability (the SMAS-30) in aging individuals. SMA refers to the core behavioral and cognitive abilities which presumably contribute to sustainable well-being in later life. Robust findings of the studies (n=275 and n=1338) showed that SMA could be measured reliably as a composite concept of abilities systematically linked to dimensions of well-being in adults aged 65 and over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(135 citation statements)
references
References 39 publications
5
125
0
5
Order By: Relevance
“…In order to be able to evaluate the effectiveness of these interventions, the 'blueprint' has also been used as the basis for the development of a measurement instrument to measure the level of self-management ability, the Self-Management Ability Scale (SMAS-30). Results of two scale development studies that we have conducted (Schuurmans et al 2005) show that the scale has good psychometric properties. Moreover, structural equation modelling has shown that the matrix model of abilities and dimensions of wellbeing gives a very good fit to the data, compared to models of only the abilities or only the dimensions of wellbeing (see Schuurmans et al 2005).…”
Section: Criteria For Success: Overall Wellbeing and Its Dimensionsmentioning
confidence: 93%
See 1 more Smart Citation
“…In order to be able to evaluate the effectiveness of these interventions, the 'blueprint' has also been used as the basis for the development of a measurement instrument to measure the level of self-management ability, the Self-Management Ability Scale (SMAS-30). Results of two scale development studies that we have conducted (Schuurmans et al 2005) show that the scale has good psychometric properties. Moreover, structural equation modelling has shown that the matrix model of abilities and dimensions of wellbeing gives a very good fit to the data, compared to models of only the abilities or only the dimensions of wellbeing (see Schuurmans et al 2005).…”
Section: Criteria For Success: Overall Wellbeing and Its Dimensionsmentioning
confidence: 93%
“…Results of two scale development studies that we have conducted (Schuurmans et al 2005) show that the scale has good psychometric properties. Moreover, structural equation modelling has shown that the matrix model of abilities and dimensions of wellbeing gives a very good fit to the data, compared to models of only the abilities or only the dimensions of wellbeing (see Schuurmans et al 2005).…”
Section: Criteria For Success: Overall Wellbeing and Its Dimensionsmentioning
confidence: 93%
“…Age and sex were considered because research has shown that female subjects have higher self-management abilities 19 and that self-management abilities decline as the subject ages. 20 Using the aforementioned criteria, 32 of the 160 subjects owning a self-management diary were selected to participate in the study. Subjects were contacted by e-mail and telephone.…”
Section: Subject Selectionmentioning
confidence: 99%
“…Self-management ability Self-management ability was measured by the self-management ability scale (SMAS-30; Schuurmans et al 2005). Eur J Ageing (2008) 5:181-190 183 This scale is based on the conceptualization of self-management ability as proposed by the self-management of well-being theory (see ''Introduction'').…”
Section: Measures/instrumentsmentioning
confidence: 99%
“…For example, people who are more selfefficacious often will also take more initiatives, and may be better able to invest, which again may lead to reinforcement spirals. The confirmatory factor-analyses that were executed in the development studies of a scale measuring this orchestrated concept of self-management ability showed that, indeed, overall self-management ability could be measured reliably as a composite concept of interrelated abilities (see Schuurmans et al 2005).…”
Section: Introductionmentioning
confidence: 99%